ADUBAÇÃO NITROGENADA DE FORRAGEIRAS DE ESTAÇÃO FRIA EM PRESENÇA E AUSÊNCIA DE TREVO BRANCO, NA PRODUÇÃO ANIMAL E DA PASTAGEM, EM ÁREA DE INTEGRAÇÃO LAVOURA PECUÁRIA - Assmann, Alceu Luiz (Scientia Agraria, 2003)
The research was carried out at Estação Experimental da Fundação Agrária de Pesquisa Agropecuária [Agrarian Foundation for Agricultural and Cattle Research] (FAPA), in Guarapuava, state of Paraná, Brazil, during the autumn/winter of 1999. The objective of the work to was verify the influence of the nitrogen input - in presence and absence of white clover - in the dynamics of the winter grass (pasture), checked by the accumulation and production of dry mass, by the animal production and by the swinging of the nitrogen with animals grazing in the system of crop-pasture rotation, on no tillage system. The experimental design was complete randomized blocks with split-plot model and with three replications. In the plots, four levels of nitrogen were tested (O, 100, 200 and 300 kg.ha-1) and, in the split-plot model, the presence and absence of white clover. Although the application of nitrogen did not interfere in the percentage of the white clover, it increased the participation of the Italian ryegrass in detriment of the oat and it reduced the percentage of discovered soil in the pasture. Growing levels of nitrogen increased in a growing linear way the accumulation and production of dry mass and the concentration of the nitrogen in the pasture. The stocking rate and liveweight gain per hectare of bovine increased with the growing levels of nitrogen. It is necessary application of over than 100 kg.ha-1 of nitrogen to obtain residual input in the soil that can be used by the cultures after the cultivation of winter grass (pasture).